Information content in sequences and its relation to protein structure prediction - Swanson, Rosemarie (Henry Stewart Talks, 2007)
Concept of information, Variation in protein sequences, Patterns, Comparison with language, Measuring information, Genetic code, Correlated substitutions, Proteins' high tolerance for substitutions, Protein structure prediction, Dependence of structure on environment
Reviewed at 2017/10/31